Model to Increase the Level of Service Using the 5S Tools, Work Standardization, SLP and Demand Forecasting in a Peruvian Quick Commerce SME - Cueto Santander, Daniela Fernanda (2023)
The digital sales market has grown significantly in recent years, especially during the global pandemic. Quick commerce companies have gained popularity due to their ability to provide quality products at the customer's doorstep in a short amount of time. To remain competitive in this industry, companies must maintain their delivery time and provide excellent service. This study aims to optimize the processes of a quick commerce company by applying four selected tools. The goal is to complete the highest number of orders within the first 15 minutes of placing an order. The proposed model includes demand forecasting, systematic layout planning, 5's, and work standardization, resulting in an 18.6% increase in the service level. This model can be replicated by other companies in the industry and serve as a basis for further research.